In-hospital costs of an admission for adhesive small bowel obstruction. Issue 1 (December 2016) - Krielen, Pepijn; van den Beukel, Barend; Stommel, Martijn; van Goor, Harry; Strik, Chema; ten Broek, Richard
Abstract Background Previous research on the costs of treatment for ASBO is outdated and often based on reimbursements, rather than true healthcare provider costs of the admission and related interventions. An accurate estimate of the true costs of treatment is necessary to understand the healthcare burden and to model cost-efficacy of adhesion strategies. The aim of this study was to provide an accurate cost estimate of the in-hospital costs for treatment of adhesive small bowel obstruction (ASBO) using micro-costing methods. Methods Consecutive patients admitted for ASBO to the Radboud University Medical Center from November 2013 to November 2015 were included. An episode of ASBO was defined as an admission for SBO with operative confirmation of adhesions or after radiological exclusion of other causes for SBO. For the purpose of generalization we used the costs of medication and interventions as provided by the Dutch Healthcare Authority and only if these were not available local hospital costs. We evaluated costs separately for operative and non-operative treatment for ASBO. Results During the study period 39 admissions for ASBO were eligible for analysis. An operative treatment was required in 19 patients (48.7 %). Mean hospital stay for ASBO with operative treatment was 16.0 ± 11 days versus 4.0 ± 2.0 days for non-operative treatment (P = 0.003). A total of 12 patients developed complications, 2 in the non-operative group (10 %) and 10 in the operative group (52.6 %;P = 0.004). Overall costs for an admission for ASBO with operative treatment were €16 305 (SD €2 513), and for non-operative treatment € 2 277 (SD € 265) (p = <0.001). The highest expenditure with operative treatment for ASBO was made for ward stay (mean €7 856, SD €6 882), OR time (mean €2 6845, SD €1 434), ICU stay (mean €2 183, SD €4 305) and (parenteral) feeding costs (mean €1797, SD €2070). A table with correction coefficient to correct for differences in price levels for goods and services between different countries has been added. Conclusion The in-hospital costs of an admission for ASBO are higher than previously thought. These costs can be used to guide hospital reimbursement policy and for the development of a cost-effective model for the use of adhesion barriers.